Increasing Quality in large scale University Courses - Inga Saatz; Andrea Kienle (FernUniversität Hagen, 2013)
Quality of education should be stable or permanently increased - even if the number of students rises. Quality of education is often related to possibilities for active learning and individual facilitation. This paper deals with the question how high-quality learning within oversized courses could be enabled and it presents the approach of e-flashcards that enables active learning and individual facilitation within large scale university courses.